2012
DOI: 10.1088/0953-4075/45/15/154005
|View full text |Cite
|
Sign up to set email alerts
|

System–environment correlations and non-Markovian dynamics

Abstract: We determine the total state dynamics of a dephasing open quantum system using the standard environment of harmonic oscillators. Of particular interest are random unitary approaches to the same reduced dynamics and system-environment correlations in the full model. Concentrating on a model with an at times negative dephasing rate, the issue of "non-Markovianity" will also be addressed. Crucially, given the quantum environment, the appearance of non-Markovian dynamics turns out to be accompanied by a loss of sy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 50 publications
(110 reference statements)
2
43
0
Order By: Relevance
“…This behavior explains the observed buildup of the quasi-equilibrium in liquid crystals. The results of this work, together with the conclusions obtained in references 11,13 , can contribute to elucidate the underlying quantum mechanisms for decoherence of open quantum systems of interacting spins, for instance the role played by quantum correlations between the observed system and the environment in the damping of the spin coherences 25,26 . Certainly, these works showed that in liquid crystals it is essential to assume the quantum character of the spin-environment coupling to explain the observed irreversible decoherence.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…This behavior explains the observed buildup of the quasi-equilibrium in liquid crystals. The results of this work, together with the conclusions obtained in references 11,13 , can contribute to elucidate the underlying quantum mechanisms for decoherence of open quantum systems of interacting spins, for instance the role played by quantum correlations between the observed system and the environment in the damping of the spin coherences 25,26 . Certainly, these works showed that in liquid crystals it is essential to assume the quantum character of the spin-environment coupling to explain the observed irreversible decoherence.…”
Section: Discussionmentioning
confidence: 62%
“…Also, understanding the nature of the decoherence mechanism can contribute to the set up of a quantum spin-lattice relaxation theory beyond the Markovian limit, providing insight into the interplay of the quantum correlations developed in the microscopic irreversible dynamics and the dissipative macroscopic evolution. Finally, the analysis carried out in this work may contribute to the current discussion about the role of system-environment entanglement as basic mechanism of quantum decoherence of interacting particle systems 1,[25][26][27] .…”
Section: Introductionmentioning
confidence: 90%
“…Decoherence of an open system can be caused by the increase of the entanglement between system and environment [1,7,8]. Pure state is turned into mixed state as the consequence of interaction between the system and environment [2,3,7,11].…”
Section: Phase Damping Channelmentioning
confidence: 99%
“…Closed system is an ideal system that does not interact with the outside world, whereas real system has undesirable interaction with the environment [1,2]. The interaction between an open quantum system and its surroundings causes correlation between the states of the system and of the environment that is called decoherence [3].…”
Section: Introductionmentioning
confidence: 99%
“…The physical implementation and verification of our model would allow then to verify the generalization of the LGKS theorem for the simplest nontrivial commutative open quantum system. Both the single qubit dephasing case and the dephasing of two qubits in local environments, indeed, have been shown to posses a random unitary representation [19].…”
Section: The Modelmentioning
confidence: 99%